COMMERCIAL COMPONENT OF BROILER CARCASSES GIVEN “PROBIO-BALITANI” PROBIOTICS WITH DIFFERENT CONCENTRATIONS - A.A.A.A., Ratnadewi,; Mudita, I M.; Siti, N.W. (Jurnal Peternakan Tropika; Vol 12 No 5 (2024): Vol. 12 No. 5 Tahun 2024; September - October, 2024)
This research aims to understand the commercial components of broiler chicken carcasses given Probio-BaliTani probiotics at different levels. The research was conducted for 5 weeks (35 days) in Peguyangan Kaja, using a completely randomized design (CRD) consisting of 7 treatments and 4 repetitions. These treatments include: broilers without probiotics (P0), broilers given probiotics through drinking water at levels of 0.025% (P1), 0.05% (P2), 0.1% (P3), 0.5% (P4), 1% (P5), and a combination of various levels (P6). The variables measured are the weight of carcass components such as breast, back, upper thigh, lower thigh and wings. The results showed that giving Probio-BaliTani probiotics in treatments P1 to P6 could increase slaughter weight, carcass weight and broiler carcass percentage. The most effective probiotic concentration was 0.025% (P1), which significantly increased the weight of the chest, back, upper thighs, lower thighs, and wings by 15.54%, 14.44%, 13.21%, 8, respectively. 28%, and 4.58% compared to broilers without probiotics. In conclusion, the addition of Probio-BaliTani probiotics at a level of 0.025% effectively increased the weight of commercial components of broiler carcasses at 35 days of age.